Clinical study on the treatment of acute epidural hematoma by embolization of middle meningeal artery through radial artery access combined with minimally invasive burr hole drainage - Cui Zhang; Qingbo Wang; Chenglong Li; Zixuan Jing; Xinyu Zhao; Yang Chen; Zefu Li (Frontiers in Neurology)
ObjectivesThis study aims to evaluate the clinical effectiveness of using coil embolization via radial artery access, combined with drilling and drainage, as a minimally invasive treatment for acute epidural hematoma compared to traditional craniotomy.Materials and methodsA retrospective analysis was conducted on 134 patients with acute epidural hematoma treated at the Department of Neurosurgery, Binzhou Medical University Hospital, between January 2020 and April 2023. Among these patients, 37 underwent embolization of the middle meningeal artery through radial artery access combined with burr hole drainage, while 97 patients underwent craniotomy for hematoma removal. The 37 patients treated with embolization were designated as the experimental group, while the remaining 97 patients formed the control group. General patient characteristics, operation duration, intraoperative blood loss, postoperative complications, and Glasgow Coma Scale (GCS) scores upon admission and discharge were recorded and compared between the two groups.ResultsIn comparison to the control group, the experimental group exhibited higher rates of postoperative hematoma residuals and longer average postoperative drainage times. Nevertheless, the experimental group demonstrated several advantages including shorter operation durations, reduced intraoperative bleeding, lower rates of postoperative rebleeding and complications, as well as decreased requirements for postoperative blood transfusions and transfusion volumes.ConclusionThe surgical approach involving coil embolization via radial artery access combined with minimally invasive burr hole drainage yields favorable clinical outcomes. This technique presents as a viable treatment option for acute epidural hematoma resulting from middle meningeal artery hemorrhage.